Effect of Iron Accumulation on Bone Mineral Density in Patients Diagnosed With Transfusion-Dependent Thalassemia - Cem Selim; Rafiye Çiftçiler; Ayşe Hilal Eroğlu Küçükdiler; Fatma Keklik Karadağ; Nur Soyer (International Journal of Clinical Practice)
Conclusion: Our investigation has demonstrated that in patients with TDT, elevated transferrin saturation may be a sign of osteoporosis.